Thermal effect of chronic mobile phone radiation exposure at frequen-cy 1800 MHz on adult Sprague-Dawley rats - Ali S. H. Alchalabi; Erkihun Aklilu; Abd Rahman Aziz; Mohd Azam Khan Goriman Khan (2016)
The mobile communication technology, although integral to our everyday life, has been accounted to suffer negative impacts on the living body via two effects, thermal and non-thermal. The aims of this study were to assess the thermal effects by using Infra-red camera techniques and thermographic analysis and to find out how much electromagnetic fields from mobile phones contribute to increase the skin temperature due to thermal effects from chronic exposure to Global System for Mobile communication (GSM) mobile phone radiation. Eighty female Sprague Dawley rats were employed throughout the experiment, and the animals were dealt into four groups, control, 15, 30 and 60 days respectively (n=20) for 1h/day whole body expo-sure at SAR levels of 0.048 W/Kg. GSM-like signals at a frequency of 1800 MHz were provided by a signal generator. Thermographic analysis was done by using FLIR Tool software to estimate the changes in skin temperature in different regions of the physical structure. Statistical analysis shows signifi-cant changes in skin temperature between unexposed and exposed groups for 15 and 30 days of exposure (P< 0.001). While the skin temperature of 60 days exposure group remained consistent with unexposed group values. Our data suggest that mobile phone radiation at frequency 1800 MHz has a ther-mal effect represented by skin temperature rises in the whole body. The infra-red image analysis results are anticipated to help change mobile phone users' behavior to minimize the negative effects of mobile phone radiation.